Evaluasi Sifat Kimia Tanah Inceptisol Pada Kebun Inti Tanaman Gambir (Uncaria gambir Roxb.) di Kecamatan Salak Kabupaten Pakpak Bharat - Ryan Arviandi; Abdul Rauf; Gantar Sitanggang (Jurnal Agroekoteknologi, 2015)
Evaluation of Inceptisol soil chemical in Gambir Core Garden in the Sub district of Salak Pakpak Bharat District has been conducted from March 2013 to June 2013. This study aimed to evaluate the soil chemical (pH, N, P, K, CEC, Organic Carbon, Exchangable Aluminuim) based on land position on the Gambir Core Garden of Pakpak Bharat District. The method used in this research is descriptive method by conducting surveys and soil sampling based land position on the top of the hill, hillside and part of the valley. The results show the value of N and Organic Carbon are tends to rise in the valley compared to the top of the hill and the hillside. As for the value of CEC and Exchangable Aluminium are tend to rise on the hillside compared to to the top of the hill and the valley, while the value of pH, P and K are relatively same.Keyword: land position, soil chemical, gambir (Uncaria gambir Roxb.)